KEMAMPUAN MENULIS PERSUASI MENGGUNAKAN MEDIA GAMBAR SISWA KELAS VIII SMPN 14 KOTA JAMBI - Sena Febrianti; Agus Setyonegoro; Priyanto Priyanto; Andiopenta Purba; Akhyaruddin Akhyaruddin (Universitas Negeri Makassar, 2024)
This study aims to describe the ability to write persuasion using image media in class VIII students of SMPN 14 Jambi City using a quantitative descriptive approach. The number of subjects in this study was 31, namely class VIII A. The data research instrument in this study was a performance test for writing persuasive text. Assessment in writing persuasive text is based on the structure and linguistic rules, namely the existence of a series of arguments, facts, invitations, and the use of argumentative conjunctions. Furthermore, students write persuasive texts using image media. Data analysis in this study is the work of students who are examined by two assessors, namely teachers and researchers. The results of this study show that the ability to write persuasive texts using image media of class VIII A students in the aspect of writing a series of arguments gets an average score of 77, the ability to write facts gets an average score of 73.5, writing invitations gets an average score of 74.8, and the ability to use linguistic rules gets an average score of 75.4.